Dynamics of Store Image and Customer Commitment in Retail: Mediation Analysis - Sisodia, Gyanendra Singh; Raut, Umesh Ramchandra; Pawar, Prafulla Arjun; Khandelwal, Rahul (Journal of Posthumanism, 2025)
The study examines the role of store satisfaction and Trust as mediators between business image and customer commitment. This study employed appropriate research methods and sample design to accomplish its purpose. At first, the research design verified the dependability and accuracy of the measurement scale. In addition, a statistical analysis was conducted to examine the impact of retail store image, satisfaction, and trust on retail store commitment. The study found that the store image plays the role of an influencer. In contrast, store satisfaction and Trust mediate the consumer relationship through customer commitment towards the retail store when retailers think about the store image. The present study tests the measurement model and mediating path model to confirm the measurement model's dimensionality, validity and reliability. The present study provides the platform to measure customer commitment by considering various associated variables with customer commitment.